2009
DOI: 10.2527/jas.2009-1778
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of modern technologies commonly used in beef cattle production: Conventional beef production versus nonconventional production using meta-analysis

Abstract: Conventional feeding systems use pharmaceutical products not allowed in natural or organic systems for finishing cattle. This review of data compares the performance effects (ADG, G:F, DMI) of technologies used in conventional feeding programs that are prohibited in organic programs, natural programs, or both. The technologies evaluated were steroid implants, monensin, tylosin, endectocides, and metaphylaxis with any antimicrobial. For inclusion in this analysis, studies were conducted in North America, report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 20 publications
6
58
1
2
Order By: Relevance
“…In year 2, TYL also improved gain:feed compared with Control cattle in the backgrounding period in accordance with previous research by Brown et al (1975) and Meyer et al (2009), although Wileman et al (2009) found that feeding TYL did not show a consistent advantage relative to Control cattle with respect to ADG, gain:feed or DMI. However, the observed reduction in DMI in year 2 during the finishing period and overall with TYL relative to all other treatments is inconsistent with other studies (Meyer et al 2009).…”
Section: Animal Performancesupporting
confidence: 80%
See 2 more Smart Citations
“…In year 2, TYL also improved gain:feed compared with Control cattle in the backgrounding period in accordance with previous research by Brown et al (1975) and Meyer et al (2009), although Wileman et al (2009) found that feeding TYL did not show a consistent advantage relative to Control cattle with respect to ADG, gain:feed or DMI. However, the observed reduction in DMI in year 2 during the finishing period and overall with TYL relative to all other treatments is inconsistent with other studies (Meyer et al 2009).…”
Section: Animal Performancesupporting
confidence: 80%
“…Although feeding subtherapeutic antimicrobials did not confer consistent performance advantages under the experimental conditions of the present study, the option of directly purchasing calves from a single source would not be available to most commercial feedlots, and housing cattle in small pens of 10 steers would undoubtedly raise costs. Similarly, Wileman et al (2009) estimated that a $78 per animal premium would be necessary for commercial beef production without the use antimicrobial metaphylaxis on arrival at the feedlot or tylosin in diets, due to predicted reductions in ADG and increases in liver abscesses, morbidity and mortality. The results of the present study demonstrate that low-risk cattle raised in small pens may have similar growth performance, health status and carcass characteristics to cattle fed subtherapeutic antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of action of tylosin is believed to be its inhibitory effect on F. necrophorum in the rumen, in the liver, or both (Nagaraja and Lechtenberg, 2007). A meta-analysis on liver abscess risks of cattle receiving tylosin vs. cattle not receiving tylosin in conventional feeding systems showed that the feeding of tylosin reduced the risk of liver abscesses from 30% to 8% (Wileman et al, 2009). The incidence of liver abscesses in tylosin-fed cattle may be because of the development of resistance in F. necrophorum or abscesses caused by bacteria other than F. necrophorum.…”
Section: Controlmentioning
confidence: 99%
“…It is imperative to improve cattle growth efficiency and decrease the time to get animals to market. One particular technology, hormone implants, have been FDA approved for use in beef cattle production since 1957 (Raun, 2002) and are considered the single best management tool to improve feed efficiency and average daily gain in beef cattle (Wileman, 2009;Hermesmeyer, 2000;Johnson, 1998;Lawrence, 2007). The use of hormonal implants in cattle improve ADG, DMI, HCW and lower feed-to-gain ratios when compared to non-implanted cattle (Reinhardt, 2014).…”
Section: Introductionmentioning
confidence: 99%